2022
DOI: 10.3390/jcm11113248
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Study Using OCTA in Subjects at High Genetic Risk of Developing Alzheimer’s Disease and Cardiovascular Risk Factors

Abstract: In 103 subjects with a high genetic risk of developing Alzheimer’s disease (AD), family history (FH) of AD and ApoE ɛ4 characterization (ApoE ɛ4)) were analyzed for changes in the retinal vascular network by OCTA (optical coherence tomography angiography), and AngioTool and Erlangen-Angio-Tool (EA-Tool) as imaging analysis software. Retinal vascularization was analyzed by measuring hypercholesterolemia (HCL) and high blood pressure (HBP). Angio-Tool showed a statistically significant higher percentage of area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…In addition to brain changes, given the close relationship of this structure with the retina, retinal changes observed by optical coherence tomography (OCT) have opened up new research paths. Previously, in subjects with significant genetic risk factors for the development of AD (family history and carrier of the ApoE ε4 allele), we demonstrated that thickness changes appear in different retinal layers [7], as well as in the choroidal [14] and retinal vasculature [15]. Furthermore, in these subjects, the sectors of the retina that have volume changes have been correlated with brain areas involved in AD such as the lingual gyrus, the entorhinal cortex, and the hippocampus [16].…”
Section: Introductionmentioning
confidence: 85%
“…In addition to brain changes, given the close relationship of this structure with the retina, retinal changes observed by optical coherence tomography (OCT) have opened up new research paths. Previously, in subjects with significant genetic risk factors for the development of AD (family history and carrier of the ApoE ε4 allele), we demonstrated that thickness changes appear in different retinal layers [7], as well as in the choroidal [14] and retinal vasculature [15]. Furthermore, in these subjects, the sectors of the retina that have volume changes have been correlated with brain areas involved in AD such as the lingual gyrus, the entorhinal cortex, and the hippocampus [16].…”
Section: Introductionmentioning
confidence: 85%
“…Past studies have found significant reductions in retinal thickness and retina vascular parameters in ApoE positive patients compared to gene-negative control group. In particular, SRCP vessel density (VD) and perfusion density (PFD) were significantly reduced [5,6], as was DRCP VD [5,7]. In addition, people with a FH+ and those who carry the ApoE gene also have significantly reduced RPC VD and capillary flux index compared to healthy controls (HC) [6,7].…”
Section: Family History Of Ad (Fh+) and Apoe Genementioning
confidence: 99%
“…In the study of retinal vascular diseases, many previous studies have shown that changes in the DCP are critical. These changes include ischemia and reperfusion in the DCP area, as well as the formation of new blood vessels, which have a significant impact on the final prognosis of the disease [9]. Due to the non-invasive and high-resolution characteristics of OCTA technology, we are able to visually observe the capillary network in the macular area.…”
Section: Introductionmentioning
confidence: 99%